Contribución de Acacia mangium en el aporte de fósforo en un sistema silvopastoril con Brachiaria humidicola bajo suelos ácidos - Velasco, Ana C. (1999)
This study was conducted at the IDIAP experimental station of Calabacito, Panamá (mean annual rainfall of 2500 mm and temperature of 27 °C; soils are acid with high Al saturation), to determine the effect of the timber tree Acacia mangium on total, available and organic soil P. The treatments were: 1) Brachiaria humidicola monoculture; 2) B. humidicola in mixture with a low density (120 trees ha exponente -1) of A. mangium; and 3) B. humidicola in mixture with a high density (240 trees ha exponente -1) of A. mangium. Total and available soil P was significantly (p < 0.05) lower in the dry compared to the wet season (227 vs 259; 1.7 vs 3.7 mg l exponente -1, respectively). Mixtures of A. mangium had higher total, available and organic P with values of 232, 253 and 292; 81, 92 and 99; 2.7, 3.8 and 4.5 mg l exponente -1 for B. humidicola monoculture and low and high density A. mangium pastures respectively. It is concluded that the integration of A. mangium in B. humidicola pastures contributed to significant improvements in soil P.